RETRACTED: Alhakamy et al. Ceftriaxone and Melittin Synergistically Promote Wound Healing in Diabetic Rats. Pharmaceutics 2021, 13, 1622 - Nabil A. Alhakamy; Giuseppe Caruso; Basma G. Eid; Usama A. Fahmy; Osama A. A. Ahmed; Ashraf B. Abdel-Naim; Abdulmohsin J. Alamoudi; Shareefa A. Alghamdi; Hadeel Al Sadoun; Basmah M. Eldakhakhny; Filippo Caraci; Wesam H. Abdulaal (MDPI AG, 2024)
The journal retracts the article, "Ceftriaxone and Melittin Synergistically Promote Wound Healing in Diabetic Rats" [...]